Detection of Respiratory Viruses in Deceased Persons, Spain, 2017 - Navascués, Ana (Emerg Infect Dis, 2018)
During the 2016–17 influenza season in Spain, we tested specimens from 57 elderly deceased persons for respiratory viruses. Influenza viruses were detected in 18% of the specimens and any respiratory virus in 47%. Only 7% of participants had received a diagnosis of infection with the detected virus before death.